2021
DOI: 10.3126/rnjds.v4i1.38041
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Covid-19 on Remittance Economy of Nepal

Abstract: Remittance in Nepal before the Covid-19 outbreak was the largest source of microeconomic stability since it has contributed 26 percent of the total Gross Domestic Product. Indeed, it is a principal income of the workers’ household since 55.8 percent of the Nepalese households have been receiving it. As expected, the potential inflow of remittance after Covid-19 decreased massively and it has an unprecedented adverse effect on the overall Nepalese economy, downsizing from national-level income to everyday livin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The study highlighted that remittances were the largest source of microeconomic stability in Nepal before the pandemic, contributing significantly to the country's GDP. However, the potential inflow of remittances decreased significantly after the outbreak, adversely affecting the overall Nepalese economy and everyday living patterns, particularly in rural areas (Kafle, 2021). Consequently, these observations underscore the importance of remittances as a valuable mechanism for improving the well-being of households and their potential contribution towards promoting sustainable development in Nepal.…”
Section: Impact Of Remittances On Consumption and Household Welfarementioning
confidence: 94%
See 1 more Smart Citation
“…The study highlighted that remittances were the largest source of microeconomic stability in Nepal before the pandemic, contributing significantly to the country's GDP. However, the potential inflow of remittances decreased significantly after the outbreak, adversely affecting the overall Nepalese economy and everyday living patterns, particularly in rural areas (Kafle, 2021). Consequently, these observations underscore the importance of remittances as a valuable mechanism for improving the well-being of households and their potential contribution towards promoting sustainable development in Nepal.…”
Section: Impact Of Remittances On Consumption and Household Welfarementioning
confidence: 94%
“…On the other hand, a study by Kafle (2021) indicated the effect of the COVID-19 pandemic on the remittance economy of Nepal. The study highlighted that remittances were the largest source of microeconomic stability in Nepal before the pandemic, contributing significantly to the country's GDP.…”
Section: Impact Of Remittances On Consumption and Household Welfarementioning
confidence: 99%